Pengaruh Kualitas Pelayanan Petugas Pajak, Sanksi Perpajakan, Dan Biaya Kepatuhan Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Kota Padang - Rexy Anugerah Pratama; Erly Mulyani (Universitas Negeri Padang, 2019)
This research aims to determine whether the service quality of officers taxes, tax sanctions and tax compliance costs have a significant influence towards good compliance of MSME Taxpayers (micro, small and medium enterprises) partial or simultaneous. Data obtained from questionnaires filled out by respondents who registered with the Office of Cooperatives and MSMEs Padang. A total of 95 the questionnaire returned with a complete and processed condition. By using multiple regression techniques, the results of the study show that service quality and tax sanctions have a positive effect on MSME Taxpayer compliance. More and more both the service quality of tax officers and the increasingly heavy taxation sanctions imposed on SME Taxpayers, it will increase taxpayer compliance MSMEs. In addition, tax compliance costs have a negative effect on compliance MSME Taxpayers. The greater the tax compliance fee, the taxpayer compliance MSMEs will decline.